Melorheostosis Involving the Cervical and Upper Thoracic Spine: Radiographic, CT, and MR Imaging Findings - Motimaya, A.M.; Meyers, S.P. (American Journal of Neuroradiology, 2006)
SUMMARY: Melorheostosis, an uncommon mesenchymal dysplasia, rarely affects the axial skeleton. We describe the imaging findings of melorheostosis involving the cervical and upper thoracic spine. Radiographs and CT showed unilateral well-marginated undulating zones of cortical hyperostosis involving multiple vertebrae that were contiguous with a coalescent ossified right paravertebral mass. MR imaging showed zones of signal intensity void on all pulse sequences without contrast enhancement. Conservative management was elected because of lack of interval clinical and imaging changes for 8 years.